Biological properties and conformational studies of amphiphilic Pd(II) and Ni(II) complexes bearing functionalized aroylaminocarbo-N-thioylpyrrolinate units - Poyraz, Samet; Belveren, Samet; Aydınoğlu, Sabriye; Ulger, Mahmut; de Cózar, Abel; de Gracia Retamosa, Maria; Sansano, Jose M.; Döndaş, H. Ali (Beilstein Journal of Organic Chemistry, 2021)
A series of novel palladium(II) and nickel(II) complexes of multifunctionalized aroylaminocarbo-N-thioylpyrrolinates were synthesized and characterized by analytical and spectroscopic techniques. The biological properties of the freshly prepared compounds were screened against S. aureus, B. subtilis, A. hydrophila, E. coli, and A. baumannii bacteria and antituberculosis activity against M. tuberculosis H37Rv strains. Also, the antifungal activity was studied against C. albicans, C. tropicalis, and C. glabrata standard strains. A deep conformational survey was monitored using DFT calculations with the aim to explain the importance of the final conformation in the biological experimental results.
Keywords: antituberculosis; bidentate ligands; DFT; nickel; palladium